The Genetic Polymorphisms in the MIR17HG Gene Are Associated with the Risk of Head and Neck Squamous Cell Carcinoma in the Chinese Han Population. (24th November 2020) - Xu, Chongwen; Han, Peng; Ren, Wanli; Dai, Hao; Bai, Yanxia; Shen, Zhen; Li, Baiya; Shao, Yuan
Abstract : Purpose . Head and neck squamous cell carcinoma (HNSCC) is the most common malignant tumors in the world. Genetic variants have an important role in HNSCC progression. Our study is aimed at exploring the relationship between MIR17HG polymorphisms and HNSCC risk in the Chinese Han population. Methods . We recruited 537 HNSCC cases and 533 healthy subjects to detect the correlation of six polymorphisms in MIR17HG with HNSCC susceptibility. The associations were evaluated by computing odds ratios (ORs) and 95% confidence intervals (CIs) using logistic regression analysis. Results . Our study revealed that rs7336610 (OR 1.77, 95 % CI = 1.09 ‐ 2.86, and p = 0.021 ) and rs1428 (OR 1.73, 95 % CI = 1.07 ‐ 2.81, and p = 0.025 ) are strongly associated with increased susceptibility to HNSCC in men. Besides, rs17735387 played a crucial protective role in stage III/IV HNSCC patients (OR 0.34, 95 % CI = 0.12 ‐ 0.95, and p = 0.040 ) compared with stage I/II. Conclusion . Our study firstly indicated that MIR17HG polymorphisms are significantly associated with HNSCC susceptibility, which suggests that MIR17HG has a potential role in the occurrence of HNSCC.